The structure of the lexical component in a lexico-conceptual knowledge base - Negro Alousque, Isabel (Onomázein, 2011)
In the last years a language model, the Lexical Constructional model (mairal & Ruiz de mendoza, 2008, 2009; Ruiz de mendoza & mairal, 2008) has been developed to account for all facets of meaning, including pragmatic and discourse phenomena. Recent research in the LCm (Periñán & Arcas, 2004, 2005, 2007a, 2010a, 2010b) has built an online lexico-conceptual base, FunGramKB, for natural language processing (nLP) applications. FunGramKB consists of two levels of information (i.e. a lexical level and a conceptual level) which in turn comprise several modules. The present contribution focuses on the lexicon, one of the two modules in the lexical level. The aim of the paper is twofold: first, to analyse the FunGramKB lexical component; second, to illustrate the semantic representation in the lexicon of the concepts stored in the ontology through a contrastive analysis of the French and english lexical entries for speech act predicates.